2008
DOI: 10.1038/nm1712
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphic effects of Notch signaling in bone homeostasis

Abstract: Notch signaling is a central mechanism for controlling embryogenesis. However, its in vivo function during mesenchymal cell differentiation, and specifically, in bone homeostasis remains largely unknown. Here, we show that osteoblast-specific gain of Notch function causes severe osteosclerosis due to increased proliferation of immature osteoblasts. Under these pathological conditions, Notch stimulates early osteoblastic proliferation by up-regulating Cyclin D, Cyclin E, and Osterix. Notch also regulates termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
354
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(383 citation statements)
references
References 37 publications
22
354
2
5
Order By: Relevance
“…Notch signaling is essential for maintaining the stem cell niche in various organs 28, 29, 30, 31. Regarding its functions in the liver, it was originally implicated in the regulation of the terminal differentiation of HPCs into biliary epithelial cells23 and/or ductal structure formation in liver development 32, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is essential for maintaining the stem cell niche in various organs 28, 29, 30, 31. Regarding its functions in the liver, it was originally implicated in the regulation of the terminal differentiation of HPCs into biliary epithelial cells23 and/or ductal structure formation in liver development 32, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…(38,48) For this reason, it was expected that Notch1 could be a possible regulator of Runx2 signaling in osteoblast differentiation. However, one can ask whether normal osteoblast differentiation can occur regardless of the presence of Notch1.…”
Section: Discussionmentioning
confidence: 99%
“…Engin and colleagues suggested that Notch1 represses osteoblast maturation through the binding of Notch1-IC to Runx2. (38) However, several reports have shown that osteoblast cells expressed Notch1, and BMP-2 did not have an appreciable effect on Notch1 expression. (39)(40)(41) Moreover, osteoblast differentiation can occur despite Notch1 expression.…”
Section: Introductionmentioning
confidence: 96%
“…Key genes for the regulation of embryonic organogenesis (Hoxa5, Hoxa9, Foxc1 and Foxf2) and the commitment of immature cells to multiple lineages (Pparg, Cebpa, Plxnd1, Egfl7, Mgp, Plxdc2, Ebf1 and Tcf3) were expressed at higher levels in AO cells than in AX cells, suggesting that AO cells have characteristics of immature mesenchymal cells (Wang and Reed, 1993;Luo et al, 1997;Wu et al, 1999;Rosen et al, 2000;Parker et al, 2004;Torres-Vazquez et al, 2004;Miller et al, 2007;Cole et al, 2008). The profile of AX cells, on the other hand, was indicative of both cells that are committed to the osteocyte lineage (Dlx3, Sp7, Dkk1, Ostn and Bmp3) and cells that are inclined to tumorigenesis in vivo (Cd276, Ptgs2, Vegfa, Epha2, Frzb and Sfrp1) (Kim et al, 1993;Daluiski et al, 2001;Dannenberg et al, 2001;Thomas et al, 2003;Lee et al, 2004 Zang et al, 2007;Brantley-Sieders et al, 2008;Engin et al, 2008;Li et al, 2008).…”
Section: Ao and Ax Cells Differ In Their Gene Expression Profilesmentioning
confidence: 97%